Perlindungan Hukum bagi Pekerja Toko Modern yang Terkena Pemutusan Hubungan Kerja (PHK) secara Sepihak Akibat Dampak Pandemi Covid-19 di Kota Denpasar - Gusti Ayu Arya Anindyanari Auliani Dewi; I Nyoman Putu Budiartha; Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
The termination of the work bond was still often carried out by business owners to their workers. Among other things, modern shop owners in denpasar did as a result of the covid-19 impact of Indonesia. They make stops on modern shop workers without prior deliberations. The issue that arises is how the legal rights and protection arrangement for workers can be laid off unilaterally by the owners. The study of law is an empirical law study. Data from writing comes from debriefing and research literature. In an effort to provide legal protection against unilateral layoffs from modern shop workers, the government has issued several rules relating to the termination of employment agreements by business owners. Furthermore, the rights of unemployed workers should be noted such as severance pay and repayment and guarantee legal protection by giving preventive and repressive protection to prevent overworked owners from using unemployment.